Registration of Priority Rights to Building Use Rights Certificates (HGB) Registered In The Name of a Bankrupt Legal Entity - Sihite, Salmon; Widjaja, Gunawan (Dinasti Research, 2025)
The purpose of this study is to examine the legal certainty of Priority Rights holders as outlined in Government Regulation No. 18 of 2021 concerning the Registration of Rights for holders of Building Use Rights (HGB) if the rights holder has been declared bankrupt. It also examines the responsibility of the National Land Agency (BPN) in issuing certificates in the legal protection of third parties who have signed a Deed of Sale and Purchase (AJB) and Sale and Purchase Agreements (PPJB) made before a notary or privately as a form of legal protection and legal certainty for the community before the company is declared bankrupt, while the HGB on the land has not been registered/separated from the certificate. This study uses a normative legal method with three main approaches, namely: a legislative approach, which examines various related regulations such as the 1945 Constitution, the 1960 Basic Agrarian Law (UUPA), Law No. 20 of 1961, and Government Regulation No. 24 of 1997 in conjunction with Government Regulation No. 18 of 2021 to understand the legal and ontological basis of the issue being studied, a historical approach, and a philosophical approach. The analysis was conducted by combining inductive and deductive methods. The results of the study show that the National Land Agency (BPN) continues to provide legal certainty for holders of Priority Rights to Land Use Rights (HGB), including in bankruptcy cases, by taking into account the protection of third parties who have signed a Deed of Sale and Purchase Agreement (AJB) or a Letter of Intent to Purchase (PPJB) in accordance with the provisions of Government Regulation No. 18/2021.